Lo imaginario: Un posible acercamiento entre Bachelard y Castoriadis - Campos Salas, Jeannette (2012)
This article stablishes some paralelisms beetwen the conception of the imaginary in Gastón Bachelard with the imaginary like creation in the social-historic domain of Cornelius Castoriadis. In same way it analizes the ontology of the creative image in Bachelard and the ontology of the social phenomenon in Castoriadis.